Analysis Of The Use Of Learning Video Media In Arts And Culture Subjects In Improving Elementary School Students' Learning Motivation - Nurista, Pauli; Kalifah, Diah Rizki Nur (Jurnal Terapan Pendidikan Dasar dan Menengah, 2025)
The purpose of this study was to determine the use of video media in the subject of Arts and Culture in increasing the learning motivation of grade III elementary school students. The research method used classroom action research (CAR). The subjects of the study were 18 grade III students. Data collection techniques were in the form of tests, observations and documentation. The research design adopted the Kemmis and Taggart model in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. Data analysis in this study used qualitative data analysis, namely with statistical models such as tables and diagrams from the results of observations and values of each cycle and used quantitative data analysis by comparing data obtained from the implementation of cycle I and cycle II activities. The results of the study showed an increase in learning motivation after the application of video media to arts and culture subjects, this was evidenced by the average pre-cycle value of 64.18, in cycle I it obtained an average value of 72.56 and in cycle II it obtained an average value of 75.8. So it can be concluded that from cycle I and cycle II there was an increase in student learning motivation after the application of video media.